DIAGNOSTIC AND THERAPEUTIC CHALLENGES IN THE TREATMENT OF PATIENTS DURING THE COVID-19 EPIDEMIC - Jovicic, Jelena; Petrovic, Natasa; Ladjevic, Nikola; Magdalenic, Andjela; Ladjevic, Nebojsa (HEALTH CARE, 2020)
Introduction: The beginning of December 2019 is considered to be the beginning of infection with the new coronavirus (Severe Acute Respiratory Syndrome Coronavirus 2 - SARS-CoV-2), in Wuhan, China, better known among professionals as COVID-19 (Coronavirus Disease 2019 -COVID-19). Case report: A 42-year-old male was referred for examination due to suspicion of COVID-19. According to the patient, the symptoms started four days ago with nausea and cough, heavy breathing, and fever. During the examination, the patient was pale, breathed with difficulty, subfebrile, tachycardic, normotensive. A severe form of COVID 19 pneumonia was verified by the radiological examination. Laboratory parameters indicated the infectious syndrome and heart failure. On the first day of hospitalization, the general condition worsened: with the appearance of arrhythmia, then respiratory deterioration. The therapeutic support was provided according to the COVID-19 protocol. On the second day of hospitalization, the patient was intubated, followed by three-day mechanical ventilatory support, vasopressor stimulation of hemodynamics, double stimulation of diuresis. All steps provided vital parameter stabilization. Repeated Polymerase Chain Reaction (PCR) testing and bronchoalveolar lavage (BAL) testing were negative. Repeated chest x-ray indicated the significant regression of findings. A heart ultrasound was performed, which indicated a significantly reduced function of the left ventricle in comparison to the previous examination. The patient had previous cardiac co-morbidities and the cardiac surgeon gave an opinion and confirmed the need for surgical correction of aortic and mitral valves disease with the previous treatment of the infection. Two months later, reconstructive cardiac surgery was performed. Conclusion: By presenting the clinical course of the disease, diagnostic, and therapeutic approach in a patient with cardiovascular comorbidity, we wanted to point out the difficulties in recognizing the clinical picture and diagnosing COVID-19.